A pragmatic double blind remote pilot feasibility randomised controlled trial of a self-management app for people with Sjögren disease - Hackett, Katie L.; Campbell, Miglena; Pakpahan, Eduwin; Vines, John; Lendrem, Dennis; McCready, Jemma; Rapley, Tim; Ellis, Jason; Deary, Vincent; McColl, Elaine; McCallum, Claire (Frontiers in Digital Health, 2025)
ObjectivesTo pilot and assess the feasibility of a fully remote effectiveness evaluation of a novel smartphone self-management app for people living with Sjögren disease (SjD), including evaluating trial procedures and app engagement.MethodsWe conducted a double-blind, randomised, fully-remote pilot feasibility of a self-management smartphone app (Sjogo) containing interactive components with an information-only control app. After completing onboarding procedures, participants were allocated to a trial arm following download from Apple App and Google Play stores. Participants completed symptoms and quality of life measures at baseline and (at two further timepoints (5–7 and 10–13 weeks) after download. Engagement with the app was measured with number and duration of logins.Results996 participants downloaded Sjogo to their smartphone. 871 (87.45%) consented to take part in the study and 617 (61.95%) completed the onboarding procedures and baseline measures and were randomised to the full-version of the app (n = 318) or control-version (n = 299). In-app randomisation produced balanced groups. In week 1 engagement was higher in the intervention group m = 4.76 logins (S.D. 8.06) than the control group m = 3.47 (S.D. 2.75). At week 2 engagement dropped in both groups (intervention group m = 1.17, SD 4.56, control m = 0.40, SD 0.93). Outcome completion rates at subsequent timepoints were 36.63% (weeks 5–7) and 27.39% (weeks 10–13).ConclusionIt is feasible to collect data fully remotely, automate trial procedures, and recruit participants to a randomised controlled trial of a self-management smartphone app for people with SjD through app stores. However, app engagement and outcome completion rates could be improved.